Th17 Responses to Collagen Type V, kα1‐Tubulin, and Vimentin Are Present Early in Human Development and Persist Throughout Life. Issue 4 (19th December 2016) - Sullivan, J. A.; Jankowska‐Gan, E.; Hegde, S.; Pestrak, M. A.; Agashe, V. V.; Park, A. C.; Brown, M. E.; Kernien, J. F.; Wilkes, D. S.; Kaufman, D. B.; Greenspan, D. S.; Burlingham, W. J.
Abstract : T helper 17 (Th17)–dependent autoimmune responses can develop after heart or lung transplantation and are associated with fibro‐obliterative forms of chronic rejection; however, the specific self‐antigens involved are typically different from those associated with autoimmune disease. To investigate the basis of these responses, we investigated whether removal of regulatory T cells or blockade of function reveals a similar autoantigen bias. We found that Th17 cells specific for collagen type V (Col V), kα1‐tubulin, and vimentin were present in healthy adult peripheral blood mononuclear cells, cord blood, and fetal thymus. Using synthetic peptides and recombinant fragments of the Col V triple helical region (α1[V]), we compared Th17 cells from healthy donors with Th17 cells from Col V–reactive heart and lung patients. Although the latter responded well to α1(V) fragments and peptides in an HLA‐DR–restricted fashion, Th17 cells from healthy persons responded in an HLA‐DR–restricted fashion to fragments but not to peptides. Col V, kα1‐tubulin, and vimentin are preferred targets of a highly conserved, hitherto unknown, preexisting Th17 response that is MHC class II restricted. These data suggest that autoimmunity after heart and lung transplantation may result from dysregulation of an intrinsic mechanism controlling airway and vascular homeostasis. Abstract : Th17 responses to select self‐antigens are present in normal, healthy individuals.